2009
DOI: 10.1590/s1415-52732009000100008
|View full text |Cite
|
Sign up to set email alerts
|

Validade relativa de um questionário de freqüência alimentar para utilização em adultos

Abstract: R E S U M O ObjetivoValidar um questionário semiquantitativo de freqüência alimentar para avaliar a ingestão dietética de adultos na cidade de Viçosa, Minas Gerais. MétodosNoventa e quatro adultos de ambos os sexos e representando diferentes níveis educacionais. Como método de referência para o estudo de validação, quatro recordatórios 24 horas foram usados com intervalos de um mês. Um questionário semiquantitativo de freqüência alimentar constituído de 58 itens alimentares foi aplicado no final do estudo. Os … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 23 publications
2
10
0
5
Order By: Relevance
“…This overestimation may be explained by the characteristics of the instrument, such as the perception of the portion consumed, memory and frequency of use that are established. 5 When the nutrients were adjusted for energy, different behaviors were observed among the nutrients, because some correlation coefficients increased (protein, iron, potassium, selenium, zinc and sodium) and others decreased (carbohydrate, fat, fiber, calcium and vitamins A, C and E), as found by Crispim et al, 26 Zanolla et al 23 and Lima et al 25 According to Willett, In the study by Crispim et al, 26 after adjusting for total energy intake, it was found that the correlations for macronutrients decreased, while the correlations for micronutrients increased. As described by Zanolla et al, 23 it is important that the food frequency questionnaire should be able to correctly classify individuals according to intake levels, in order to obtain correct estimates of risk, which is essential for epidemiological studies.…”
Section: Discussionmentioning
confidence: 84%
“…This overestimation may be explained by the characteristics of the instrument, such as the perception of the portion consumed, memory and frequency of use that are established. 5 When the nutrients were adjusted for energy, different behaviors were observed among the nutrients, because some correlation coefficients increased (protein, iron, potassium, selenium, zinc and sodium) and others decreased (carbohydrate, fat, fiber, calcium and vitamins A, C and E), as found by Crispim et al, 26 Zanolla et al 23 and Lima et al 25 According to Willett, In the study by Crispim et al, 26 after adjusting for total energy intake, it was found that the correlations for macronutrients decreased, while the correlations for micronutrients increased. As described by Zanolla et al, 23 it is important that the food frequency questionnaire should be able to correctly classify individuals according to intake levels, in order to obtain correct estimates of risk, which is essential for epidemiological studies.…”
Section: Discussionmentioning
confidence: 84%
“…Álbum com desenhos de alimentos e utensílios foi utilizado para minimizar erros na estimativa da quantidade consumida. No geral, esses autores 13 analisaram a validade de QFA com manual fotográfico desenvolvido para adultos da cidade de Viçosa, Minas Gerais, e obtiveram média dos coeficientes de correlação igual a 0,52 para os dados deatenuados.…”
Section: Discussionunclassified
“…No Brasil, já existem alguns álbuns fotográfi-cos elaborados com o intuito de dar suporte aos inquéritos alimentares [5][6][7][8][9] . Porém, são escassos os estudos desenvolvidos no Brasil que analisam a validade de QFA associado a fotografias de alimentos [10][11][12][13] . No país, já existem alguns QFA validados para adolescentes 10,12,[14][15][16][17][18] , sendo que um foi desenvolvido no Rio de Janeiro 19 , o qual foi avaliado quanto a sua reprodutibilidade 20 e validade 21 , tendo apresentado confiabilidade e validade relativa aceitáveis.…”
Section: Introductionunclassified
“…Embora, há muito tempo, já se soubesse que cada método de avaliação do consumo alimentar apresentava limitações, a quantificação dos erros e a validação dos métodos não eram factíveis até recentemente. Muitos estudos realizaram a validação relativa (ou calibração, como preferem alguns autores) dos métodos de inquérito alimentar, por meio da comparação com estimativas obtidas pelos diferentes métodos 5 .…”
Section: N T R O D U ç ã Ounclassified